Miktoarm Star Polymers: Branched Architectures in Drug Delivery - Victor Lotocki; Ashok Kakkar (MDPI AG, 2020)
Delivering active pharmaceutical agents to disease sites using soft polymeric nanoparticles continues to be a topical area of research. It is becoming increasingly evident that the composition of amphiphilic macromolecules plays a significant role in developing efficient nanoformulations. Branched architectures with asymmetric polymeric arms emanating from a central core junction have provided a pivotal venue to tailor their key parameters. The build-up of miktoarm stars offers vast polymer arm tunability, aiding in the development of macromolecules with adjustable properties, and allows facile inclusion of endogenous stimulus-responsive entities. Miktoarm star-based micelles have been demonstrated to exhibit denser coronae, very low critical micelle concentrations, high drug loading contents, and sustained drug release profiles. With significant advances in chemical methodologies, synthetic articulation of miktoarm polymer architecture, and determination of their structure-property relationships, are now becoming streamlined. This is helping advance their implementation into formulating efficient therapeutic interventions. This review brings into focus the important discoveries in the syntheses of miktoarm stars of varied compositions, their aqueous self-assembly, and contributions their formulations are making in advancing the field of drug delivery.